Recurrent Extreme Bilateral Gigantomastia Caused by Pseudoangiomatous Stromal Hyperplasia (PASH) Syndrome: A Case Report. Issue 1 (24th January 2023) - Parisi, Paola; Vinci, Federica; Di Meglio, Filippo; Marruzzo, Giovanni; De Luca, Alessandro; Ascione, Andrea; Vittori, Luigi; Ribuffo, Diego
Abstract : Summary: Pseudoangiomatous stromal hyperplasia (PASH) of the breast is a rare and benign medical condition in which the breast tissue is affected by an abnormal myofibroblastic proliferation, which mimics a low-grade sarcoma angiomatous proliferation. PASH usually presents itself either as a palpable mass or as an incidental diagnosis during breast specimens' histological examination. A few cases have been reported in the literature of a diffuse form of breast PASH syndrome in which the clinical presentation is a bilateral form of gigantomastia without palpable masses. In such cases, the optimal surgical management is still debated due to a significant risk of relapse after breast reduction. Mastectomy seems to be the endpoint of this condition in relapsing cases. Recent studies report a good outcome with a Tamoxifen regimen when surgery cannot be performed, supporting a hormonal component for the etiology of the condition. This study reports on an extremely rare case of bilateral, rapid, and severe PASH in a young patient, presenting as a truly disabling gigantomastia that forced the patient to use a wheelchair due to the excessive breast weights (25 kg the right breast and 21 kg the left). We describe her complicated medical history, her diagnosis, and our course of treatment.